Elevated Serum Protein S100B and Neuron Specific Enolase Values as Predictors of Early Neurological Outcome After Traumatic Brain Injury - Stefanović, Branislava (J Med Biochem, 2017)
BACKGROUND: The objective of our study was to determine the serum concentrations of protein S100B and neuron specific enolase (NSE) as well as their ability and accuracy in the prediction of early neurological outcome after a traumatic brain injury. METHODS: A total of 130 polytraumatized patients with the associated traumatic brain injuries were included in this prospective cohort study. Serum protein S100B and NSE levels were measured at 6, 24, 48 and 72 hours after the injury. Early neurological outcome was scored by Glasgow Outcome Scale (GOS) on day 14 after the brain injury. RESULTS: The protein S100B concentrations were maximal at 6 hours after the injury, which was followed by an abrupt fall, and subsequently slower release in the following two days with continual and significantly increased values (p<0.0001) in patients with poor outcome. Secondary increase in protein S100B at 72 hours was recorded in patients with lethal outcome (GOS 1). Dynamics of NSE changes was characterized by a secondary increase in concentrations at 72 hours after the injury in patients with poor outcome. CONCLUSION: Both markers have good predictive ability for poor neurological outcome, although NSE provides better discriminative potential at 72 hours after the brain injury, while protein S100B has better discriminative potential for mortality prediction.